2013
DOI: 10.1063/1.4824658
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency in 2D soap film turbulence

Abstract: The Reynolds number dependency of intermittency for 2D turbulence is studied in a flowing soap film. The Reynolds number used here is the Taylor microscale Reynolds number R_{\lambda}, which ranges from 20 to 800. Strong intermittency is found for both the inverse energy and direct enstrophy cascades as measured by (a) the pdf of velocity differences P(\delta u(r)) at inertial scales r, (b) the kurtosis of P(\partial_x u), and (c) the scaling of the so-called intermittency exponent \mu, which is zero if interm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…However the logarithmic local slope, [ln S 2 (r + ∆r) − ln S 2 (r)]/[ln(r + ∆r) − ln r] (∆r being the grid size), does not converge to a unique constant value in the IR as we decrease ν. One possibility is that the power-law exponent of S 2 (r) in the IR depends on ν (similar dependence was found for the velocity structure function of the 2D enstrophy-cascade turbulence [23]). Another possibility is that the dominant part of S 2 (r) is not a pure power law but with a correction.…”
Section: Numerical Simulation Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However the logarithmic local slope, [ln S 2 (r + ∆r) − ln S 2 (r)]/[ln(r + ∆r) − ln r] (∆r being the grid size), does not converge to a unique constant value in the IR as we decrease ν. One possibility is that the power-law exponent of S 2 (r) in the IR depends on ν (similar dependence was found for the velocity structure function of the 2D enstrophy-cascade turbulence [23]). Another possibility is that the dominant part of S 2 (r) is not a pure power law but with a correction.…”
Section: Numerical Simulation Of the Modelmentioning
confidence: 99%
“…Concerning the energy spectrum, the difference from the KLB k −3 scaling is more measurable in the gCLMG turbulence than in the 2D turbulence. The spectrum of the latter is occasionally fitted with the power law k −3.3 [16,17,[23][24][25]. Regarding the vorticity structure functions of the 2D turbulence, the result obtained in the laboratory experiment [26] showed that those of even orders up to 10 in the IR have power-law exponents indistinguishable from zero.…”
Section: Numerical Simulation Of the Modelmentioning
confidence: 99%
“…24,32,33 ). For a variable g(r) defined in space, the structure function of order q for points spaced L apart in the field is calculated from…”
Section: Characterising Intermittencymentioning
confidence: 99%
“…This observation allows a more accurate estimate of ζ q to be made, and therefore a more accurate estimate of the scaling of the power-law relation, and the intermittent properties of the data. The intermittency level may be estimated by calculating the deviation of the 6th order structure function scaling exponent ζ 6 from the non-intermittent prediction of ζ 6 /ζ 3 = 2 24,32 . This is sometimes called the intermittency exponent 24,32 , and it appears in the log-normal model of intermittency.…”
Section: Characterising Intermittencymentioning
confidence: 99%
See 1 more Smart Citation